EFEKTIVITAS PENGGUNAAN METODE STORYTELLING BERBASIS BONEKA TANGAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Khairunnisa (MGMP PAI Jawa Barat, 2023)
ABSTRACT Globally, high student learning motivation is one of the important milestones in achieving optimal learning goals. The sad fact is that after the pandemic, the learning motivation of Indonesian students has decreased by up to 70% due to unpleasant learning methods, lack of interactive learning, and lack of adequate facilities. With this high percentage, there is a need for innovation to increase student learning motivation. Learning methods and media have an important position in achieving effective learning. Collaborative learning methods and media that are fun and can be used to increase student learning motivation is the Hand Puppet Based Storytelling Method. Through this research, the researcher Kims to determine the effectiveness of using the Hand Puppet-Based Storytelling Method to increase student learning motivation, especially in elementary PAI learning. This study used a quantitative method with a one group posttest-posttest pre-experimental design. Based on the results of the findings of the researchers before the. Based on data student motivation in the experimental class increased by 52%. Furthermore, the researcher found that the percentage value of N-Gain was in the